2020
DOI: 10.1186/s12881-020-01004-2
|View full text |Cite
|
Sign up to set email alerts
|

Exons deletion of CNKSR2 gene identified in X-linked syndromic intellectual disability

Abstract: Background: The Houge type of X-linked syndromic mental retardation is an X-linked intellectual disability (XLID) recently recorded in the Online Mendelian Inheritance in Man (OMIM) and only 8 cases have been reported in literature thus far. Case presentation: We present two brothers with intractable seizures and syndromic intellectual disability with symptoms consisting of delayed development, intellectual disability, and speech and language delay. The mother was a symptomatic carrier with milder clinical phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…However, for another six mothers (three mothers in this cohort, family 14, [1]; family 15, [7]; family 16, [17], there were no reported seizures or intellectual disability. Skewed X-inactivation may be the underlying reason for this observed difference in penetrance (85:15 in the mother of family 25, [6] and 20:80 in family 26, [14], both with neurodevelopmental concerns, while reported to be 57:43 for the mother reported to have no neurological issues of family 15, [7]).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, for another six mothers (three mothers in this cohort, family 14, [1]; family 15, [7]; family 16, [17], there were no reported seizures or intellectual disability. Skewed X-inactivation may be the underlying reason for this observed difference in penetrance (85:15 in the mother of family 25, [6] and 20:80 in family 26, [14], both with neurodevelopmental concerns, while reported to be 57:43 for the mother reported to have no neurological issues of family 15, [7]).…”
Section: Discussionmentioning
confidence: 96%
“…Of the 13 affected males in our cohort, ten represent de novo cases, while in three the variants are maternally inherited. Recent articles have indicated that females harboring heterozygous CNKSR2 pathogenic variants may have seizures, with some also manifesting neurodevelopmental concerns (family 26, [14]; family 27, [2]; mother and sister of family 19, [5]; mother of family 25, [6]; mother of family 26, [20]). However, for another six mothers (three mothers in this cohort, family 14, [1]; family 15, [7]; family 16, [17], there were no reported seizures or intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serious attention deficit and hyperactivity have frequently been observed [ 53 ]. Multiple types of variations, including deletion [ 8 , 54 , 55 , 56 , 57 ], frame shift [ 54 , 57 , 58 ], splicing [ 57 , 59 ], and nonsense variations [ 53 , 57 , 60 , 61 , 62 ] have been reported in patients suffering from MRXSHG ( Figure 2 and Table 1 ). Severely affected patients were all hemizygous males and heterozygous female carriers of variants that exhibited moderate to mild phenotype or unaffected ( Table 1 ), probably because of the production of CNKSR2 from the normal allele.…”
Section: Cnksr2 and Neurodevelopmental Disordersmentioning
confidence: 99%